Conventional-Vincristine Sulfate vs. Modified Protocol of Vincristine Sulfate and L-Asparaginase in Canine Transmissible Venereal Tumor - Setthawongsin, Chanokchon; Teewasutrakul, Patharakrit; Tangkawattana, Sirikachorn; Techangamsuwan, Somporn; Rungsipipat, Anudep (Frontiers in Veterinary Science, 2019)
Background: Vincristine (VCR) is a mono-chemotherapy for canine transmissible venereal tumor (CTVT). L-asparaginase (LAP) is usually used in combination with other drugs. Previously, LAP-VCR protocol was applied for the CTVT-VCR-resistant cases. However, there were a few reports about using this protocol since the first visit. Aims: To firstly investigate the effectiveness of combining chemotherapy (Vincristine and L-asparaginase, VCR-LAP) in normal CTVT case. Secondly, to compare this protocol with the conventional (Vincristine, VCR) protocol before and during treatment in 24 CTVT dogs. Materials and Methods: Clinical signs, tumor relative volume, and histopathological change [amount of CTVT cells, tumor-infiltrating lymphocytes (TILs), TILs/CTVT ratio, collagen area, and Ki-67 proliferative index (PI)] were the treatment evaluation parameters. Moreover, transcriptome analysis of apoptotic (Bcl-2, Bax), drug-resistant genes (ABCB1, ABCG2), and BCL-2 and BAX expression were also included. Results: Both protocols gave the decreased tumor volume, increased TILs/CTVT ratios and collagen area in the mass. Interestingly, the combination protocol decreased treatment time. There were two resistant cases after treatment with VCR. The expression of Bcl-2 and Bax were decreased, and this may indicate the better response after treatment. Moreover, both drug resistant genes did not increase after treatment. Conclusion: The main finding of this study is that the combination protocol did not only decrease treatment duration time but also gave the effectiveness of treatment outcomes in CTVT cases. Therefore, the application of the new protocol could be used by the field practitioners.